Scope of Digital Manufacturing in India after Covid-19 - et. al., Dr Bharat Chede, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Digital Manufacturing has got wide Scope after COVID-19pandemic Digital Manufacturing is a wider term .in new age of manufacturing, where material and digital innovations makes the industry to achieve the desired design and quantity in shorter time period compared to conventional method. It comprise of ergonomics, human factor analysis, visualization, manufacturing simulation, product design to process and process design. After pandemic there is increase in demand of many commodity for which high rate of production is required to overcome this digital manufacturing can play vital role in overcoming this.